1975
DOI: 10.1017/s0003356100041209
|View full text |Cite
|
Sign up to set email alerts
|

Studies in sow reproduction. 3. The effect of nutrition between weaning and remating on the reproductive performance of multiparous sows

Abstract: SUMMARYAn experiment was conducted using 176 sows at three centres to investigate the effect of post-weaning feed level on reproductive performance. At two centres sows weaned 35 to 56 days after farrowing received 1·8, 2·3, 3·6 or 4·5 kg food/day from the day following weaning until the day following the last mating at the post-weaning oestrus.At the third centre sows were rationed to 1·8, 2·3 or 3·6 kg food/day or given all they would consume in a single 1-hr feeding period each day. Reproductive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…(1976) and Fahmy and Dufour (1976 but is markedly lower than the estimates reported by Rasbech (1969), Brooks, Cole, Rowlinson, Croxson and Luscombe (1975), Moody, Baker, Hays and Speer (1969); King (1974) (whose observations were based on relatively small samples). (1976) and Fahmy and Dufour (1976 but is markedly lower than the estimates reported by Rasbech (1969), Brooks, Cole, Rowlinson, Croxson and Luscombe (1975), Moody, Baker, Hays and Speer (1969); King (1974) (whose observations were based on relatively small samples).…”
Section: Discussionmentioning
confidence: 60%
“…(1976) and Fahmy and Dufour (1976 but is markedly lower than the estimates reported by Rasbech (1969), Brooks, Cole, Rowlinson, Croxson and Luscombe (1975), Moody, Baker, Hays and Speer (1969); King (1974) (whose observations were based on relatively small samples). (1976) and Fahmy and Dufour (1976 but is markedly lower than the estimates reported by Rasbech (1969), Brooks, Cole, Rowlinson, Croxson and Luscombe (1975), Moody, Baker, Hays and Speer (1969); King (1974) (whose observations were based on relatively small samples).…”
Section: Discussionmentioning
confidence: 60%
“…These data suggest that little relationship exists between sow weight loss during lactation and the interval between weaning and first estrus. The results of Brooks et al (1975), Varley and Cole (1978) and Cox et al (1983) support this conclusion. In contrast, Petherick et al (1977) reported an association between lactation weight loss and estrous activity during lactation.…”
Section: Resultsmentioning
confidence: 66%
“…Research has shown that increasing nutrient intake during the weaning to service interval can reduce the days to oestrus (Brooks et al, 1975). In this study, supplementing the LND diet with Rovabio R Excel increased energy intake during the weaning to service interval.…”
mentioning
confidence: 70%